Elementy controllingu sprzedaży w małym przedsiębiorstwie - Martyniuk, Olga (The Elements of Sale - Controlling in Small Business., 2006)
The article concerns the elements of sale - controlling such as planning, comparing results against these plans and assessing the results. The author presents reports (schedules, reports) which facilitate controlling and assessing the work of sales representatives.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 43-52